An exploration on the process of brand identity building in the context of Malaysian cafe - Mohd Rashid, Sabrina; Cohen, David A.; Ghose, Kamal (Universiti Kebangsaan Malaysia, 2018)
Identity is vital when communication takes place. Thus, building a strong brand identity has become a prime marketing concern for many business owners. In previous years, the focus was on the communication between the organisation and the customers. This study extended previous research by focusing on the business concept and identity and their approach of communicating themselves (brand) to the public, a step further in safeguarding a place in the enormous business industry. A qualitative approach with semi-structured interviews ware used to explore the food and beverage industry, focusing on independent coffee shops. The interviews were carried out with five independent coffee shops in Kuala Lumpur, Malaysia. According to the finding of this research, there is a lacking in the investment on the execution of brand for these independent coffee shops. This research also initiates that the inclusion of (the owner’s) roots, identity, and meaning of names are relevant when building an identity of a brand to have a distinctive business concept. This study contributed to our understanding of how brand identity was built and then connected it to the internal culture of the coffee shop. The findings suggested that the process of creating and building a brand identity was more complicated than just producing the visual imagery in order to build and communicate distinctively.